The Impact of Owner Gender in Family Businesses in Indonesia Liliana Dewi, Kazia Laturette, and I Gusti Bagus Yos - Dewi, Liliana; Laturette, Kazia; Wiryakusuma, I Gusti Bagus Yosia (KnE Social Sciences, 2021)
There are differences in the way people perceive the role of women and men in business. The purpose of this study was to analyze the influence of male or female leaders on two business families in Indonesia. The success of the family company cannot be separated from the role of the first generation in trusting future generations to continue their family business. A qualitative approach was used, where the data were collected through interviews with two family companies with different generations of successors. One family company has a female successor generation and another family company has a male successor. The findings showed that the first generation trusted from an early age and involved the second generation in the family business, whether their children were girls or boys. In fact, all succeeded in taking over the baton of leadership. An interesting finding is that even though the next generation is female and handles welding, which is more commonly done by men, thanks to the trust given by their parents, this next generation would be more masculine in order to gain legitimacy from employees who have worked for a long time in the company. This is as good as the next generation of men in other family companies. Keywords: family business, gender, first-generation roles, succession of success